The Volsci Volcanic Field (central Italy): eruptive history, magma system and implications on continental subduction processes - F. Marra; G. L. Cardello; M. Gaeta; B. R. Jicha; P. Montone; E. M. Niespolo; S. Nomade; D. M. Palladino; A. Pereira; G. De Luca; F. Florindo; A. Frepoli; et al. (International Journal of Earth Sciences, 2021)
Here, we report on the Quaternary Volsci Volcanic Field (VVF, central Italy). In light of new 40 Ar/ 39 Ar geochronological data and compositional characterization of juvenile eruptive products, we refine the history of VVF activity, and outline the implications on the pre-eruptive magma system and the continental subduction processes involved. Different from the nearby volcanic districts of the Roman and Campanian Provinces, the VVF was characterized by small-volume (0.01–0.1 km 3 ) eruptions from a network of monogenetic centers (mostly tuff rings and scoria cones, with subordinate lava occurrences), clustered along high-angle faults of lithospheric depth. Leucite-bearing, high-K (HKS) magmas (for which we report for the first time the phlogopite phenocryst compositions) mostly fed the early phase of activity (∼761–539 ka), then primitive, plagioclase-bearing (KS) magmas appeared during the climactic phase (∼424–349 ka), partially overlapping with HKS ones, and then prevailed during the late phase of activity (∼300–231 ka). The fast ascent of primitive magma batches is typical of a tectonically controlled volcanic field, where the very low magma flux is a passive byproduct of regional tectonic strain. We suggest that the dominant compressive stress field acting at depth was accompanied by an extensional regime in the upper crust, associated with the gravity spreading of the Apennine chain, allowing the fast ascent of magma from the mantle source with limited stationing in shallow reservoirs.